Management of Krumiroga in Paediatrics by Ayurveda: A Review (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Krumiroga, commonly known as worm infestation, is a prevalent health issue addressed in Ayurveda. This condition refers to the invasion of the human body by various types of parasites, leading to a spectrum of health disturbances. The Ayurvedic system offers a holistic approach to managing Krumiroga, emphasizing dietary regulations, herbal medications, and lifestyle modifications. Krumiroga is (worm infestation) is one of the most common disease encountered in day to day Paediatric practice. Helminthes are quite common and comprise a very large group of infestations and disease producing in children. Helminthiasis is prevalent globally (33% of world’s population harbours them), but is more common in developing countries with poorer personal and environmental hygiene. In Ayurvedic literatures, the word krumi is vague term used to denote tiny living being. Many Acharyas described krumis in various Samhitas in detail and they also believed that krimi also act as an etiological factor in various disease e.g. krumija shiroroga, hridroga etc. Because of the negligible side effects, the importance of ayurveda drugs has tremendously increased in the recent practice. A wide variety of ayurveda drugs possess anthelminthic activities which are naturally available in abundance.